Parent-child relationships and psychological distress: survey of parents from low-income families after the COVID-19 pandemic - Li Ping Wong; Haridah Alias; Nik Daliana Nik Farid; Sofia Md Yusop; Zuhrah Musa; Zhijian Hu; Yulan Lin (Frontiers Media S.A., 2023)
IntroductionThis study aims to shed light on parent-child relationships and the psychological health of parents from low-income families after the easing of the COVID-19 pandemic restrictions.MethodsThis cross-sectional study recruited 553 parents of children aged 13-24 years in low-income community settings. The Parent-Child Conflict scale of the Parental Environment Questionnaire (PEQ) was used to measure parent-child conflict. Psychological distress was assessed using the Depression, Anxiety, and Stress Scale short form (DASS-21).ResultsThe study revealed a low level of parent-child conflict in the overall study population, with a median PEQ of 48.0 (interquartile range [IQR] 36 to 48). Concerning demographics, married parents reported a likelihood of having a higher level of parent-child conflict over 3 times higher than single parents (OR = 3.18 95%, CI 1.30-7.75). More parent-child conflicts were also found in parents aged 60-72 years old who were unemployed, retired, or housewives and from lower-income groups. In regard to lifestyle factors, a higher level of physical activity and having enough sleep were associated with lower levels of parent-child conflict. Only approximately 1% of the participants reported symptoms of depression, anxiety, or stress.DiscussionLow risk exists for parent-child conflict and psychological sequelae following the easing of the COVID-19 pandemic restrictions, which could be due to various support measures implemented by the government. Vulnerable parents identified as being at risk of parent-child conflict warrant attention in future advocacy efforts.